2006
DOI: 10.1093/ecam/nel094
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Activity of Chlorophytum borivilianum Sant. F

Abstract: Chlorophytum borivilianum Santapau & Fernandes (Liliaceae) is a very popular herb in traditional Indian medicine and constitute a group of herbs used as ‘Rasayan’ or adaptogen. Ethanolic extract of the roots and its sapogenin were evaluated for their immunomodulatory activity. Effect of azathioprine-induced myelosuppresion and administration of extracts on hematological and serological parameters was determined. Administration of extracts greatly improved survival against Candida albicans infection. An increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 13 publications
3
29
0
Order By: Relevance
“…) which exert such activities. Thakur et al (2006) observed similar findings with the root extract of Chlorophytum borivilianum. The oral administration of ethanolic and water extracts of Capparis zeylanica at doses of 150-300 mg kg -1 body wt showed a similar dose-related increase in the clearance rate of carbon by the cells of the RES (Ghule et al 2006).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…) which exert such activities. Thakur et al (2006) observed similar findings with the root extract of Chlorophytum borivilianum. The oral administration of ethanolic and water extracts of Capparis zeylanica at doses of 150-300 mg kg -1 body wt showed a similar dose-related increase in the clearance rate of carbon by the cells of the RES (Ghule et al 2006).…”
Section: Discussionsupporting
confidence: 74%
“…In addition, Ghule et al (2006) also reported that Capparis zeylanica showed dose-dependent immunostimulatory activity in both alcohol and aqueous extracts. Thakur et al (2006) observed that sapogenin of ethanolic extract of Chlorophytum borivillanum induced stimulation of immune response in treated animals. In the present investigation, ethanolic and aqueous extracts of S. rebaudiana showed potent results, proving their immunostimulatory activities and showing that they could be effective candidates for the prevention of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It may use in infection condition, enhancement of immunological response against foreign particles or antigens, and improving defensive response under normal circumstances. [26] Ethanolic extract and aqueous extract of Picrorhiza kurroa have the ability to stimulate humoral response by acting various level of immune mechanism such as antibody production, release of mediators of hypersensitivity reactions, and tissue responses to these mediators in the target organs. [27] …”
Section: Effect On Innate Immune Systemmentioning
confidence: 99%
“…A rasayan may be defined as smooth prostressor, which reduces reactivity of host defense systems and decreases damaging effects of various stressors due to increased basal level of mediators involved in the stress response. 4,5 Curculigo orchioides (CO) Gaertn. (family Amaryllidaceae) is a well-known herb in traditional Indian system of medicine and has been designated as a Vajikaran Rasayan.…”
Section: Introductionmentioning
confidence: 99%